Windows NT 4 advanced programming - Rajagopal, Raj (Osborne McGraw-Hill, 1998)
This book will take a set of advanced programming topics such as database programming, Internet and network programming, multimedia programming, etc., and address the following: concept details of the programming topics the programmer should be familiar with; programming examples to illustrate the concept; programming Notes the programmer should be familiar with; error situations the programmer is likely to run into, known problems, workarounds, etc. The programmers using this book are expected to have experience developing C and/or C++ programs in the Windows environment, preferably using the Win API (Application Programming Interface) family. The average programmer typically uses a small subset of the total programming capabilities of Win APIs and NT and then comes across a need to develop applications using additional capabilities.